PENGARUH KOMUNIKASI, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA RS AWAL BROS BATAM - NOVANI SHADILLA MAHENDRA; Jontro Simanjuntak (LPPM Universitas Putera Batam, 2022)
Human resources are factors that need to be considered by a company. Human resources are a driving force for running the company and as an asset for the survival of the company, both in the short and long term. All companies must have the same goal, namely to achieve a profit and have a very small risk of loss. In order to achieve that goal, a company must maximize the use of production and non-production factors. From this phenomenon, the title of this study was taken to be investigated more deeply. This study aims to analyze whether there is an effect of communication, work discipline and work motivation on employee performance at Awal Bros Hospital Batam. This type of research uses quantitative research, with primary data conducted by distributing questionnaires to 241 respondents. The sampling technique in this study used simple random sampling method and the data analysis method used was descriptive method, validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination test, and hypothesis testing. The data was processed with the help of SPSS version 25, the results showed that the variables of communication, work discipline and work motivation had a positive and significant effect on employee performance. The results of the coefficient of determination of 0.415 indicate that the variables of communication, work discipline and work motivation affect employee performance by 41.5% and the remaining 58.5% is influenced by other variables.Abstract.